Integrated geophysical and geomatic studies at Ghar Dalam Cave, Malta's oldest prehistoric site. Issue 1 (1st April 2022) - Galone, L.; Colica, E.; D'Amico, S.; Cardona, D.; Portelli, P.; Fontanelli, F.; Borg, J.J.
Abstract: The Ghar Dalam cave, southern Malta, hosts the oldest human evidence in the Maltese archipelago. Although the internal stratigraphy of the cave and its biotic record is well studied, the possibility of archaeological / paleontological prospects in the surrounding areas requires additional studies. In this work we use aerial and ground-based photogrammetry to reconstruct the interior and the surface of the cave, and various geophysical techniques (GPR, passive seismic and ERT) to study the subsurface of the cave and its surroundings. The results have clarified the geometry of the soil-rock contact above and at the entrance of the cave and possible karstic structures have been identified. The authors conclude that this multidisciplinary methodology allows more reliable results to be achieved and is essential for studies where direct observation is not possible.